THE PRINCIPLE OF EQUITY IN THE DISTRIBUTION OF WATER RESOURCES ACCORDING ON THE CONSTITUTION OF THE REPUBLIC OF IRAQ OF 2005 - Abdul Hassan Dowaij Khafif; Prof. Dr. Walid Khashan Zghair (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
One can hardly think of a principle comparable to the principle of justice in its importance to the human being, as it is the source from which all human principles derive their value, and as long as this principle has been the focus of philosophical theories along the historical process of humanity, the Constitution of the Republic of Iraq has adopted this principle in the distribution of water resources within the state. And we tried as much as we could in this research to derive from the principle of justice a set of disciplined criteria to guide the Iraqi legislator in the event of his intention to enact a law on the distribution of water resources that the constitution wanted; Because the principle of justice is a variable principle in terms of time and place and cannot be imagined without its tools that lead to it. The study concluded a set of criteria that we suggested to the legislator to adopt in the Water Resources Distribution Law.